Kepastian Hukum Keputusan Sirkuler Di Luar Rapat Umum Pemegang Saham Atas Saham Nominee (Studi Putusan Nomor 815/PDT/2022/PT SBY) - Ulfa, Raudhah Mariyah; Putranto, Rahmat Dwi (FOCUS, 2025)
This study analyses the legal certainty of circular resolutions outside the General Meeting of Shareholders (GMS) on nominee shares based on Decision Number 815/PDT/2022/PT SBY. This study focuses on the legality and legal implications of circular resolutions in corporate practice in Indonesia. Through a normative juridical approach and analysis of relevant regulations and case law, this study finds that circular resolutions made without fulfilling formal and material requirements may be potentially legally invalid. The results of this study provide recommendations on the need for stricter law enforcement regarding the use of nominee shares in the Indonesian legal system.